(untitled) (Bangladesh Pharmaceutical Journal, 2015)
Flemingia macrophylla locally known as Charchara in Bangladesh is a medicinal herb. Being a member of the Fabaceae family it claims a number of medicinal uses including hypoglycemic activity, neuroprotective effect and gynecological remedies. Methanolic extract of F. macrophylla was investigated to evaluate its antioxidant and general toxic properties in this study. Antioxidant potential was evaluated using total antioxidant capacity, total phenol contents, total flavonoid contents and DPPH (1,1-diphenyl-2-picrylhydrazyl) assays. Both leaf and stem extracts of F. macrophylla were found to possess significant amount of phenolics and flavonoids, expressed as gallic acid equivalents (GAE) and quercetin equivalent (QE), respectively. Interestingly total phenol content was equal for both leaf and stem extract and it was 43.8 mg GAE/g. Total flavonoid content was found to be 64.4 and 39.1 mg QE/g for leaf and stem extract, respectively. The total antioxidant capacity was expressed as ascorbic acid equivalents (AAE) and for leaf it was 5.067 mg/gm AAE and for stem 0.8167 mg/gm AAE. DPPH scavenging activity was determined by comparing with ascorbic acid. The IC50 values were 19.95, 125.89 and 707.94 ?g/ml for ascorbic acid, leaf and stem extract, respectively. The results of the present study on methanolic extracts of F. macrophylla revealed the presence of moderate antioxidant activity and extract of leaves produced better results than stem of the plant. In brine shrimp lethality bioassay, methanolic extract of F. macrophylla exhibited insignificant cytotoxicity. DOI: http://dx.doi.org/10.3329/bpj.v16i2.22298 Bangladesh Pharmaceutical Journal 16(2): 159-163, 2013